(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Gender equality is the number five agenda of the Sustainable Development Goal, where its primary goal is providing women and girls with equal access to education. Up to this day, students experience gender issues, inequality, and bias inside the classroom. This research looked into the extent of observation on gender issues inside the classroom to eliminate bias, discrimination, and to achieve a comfortable classroom environment. More specifically, this research aimed to develop an intervention to address gender and development issues in the classroom. A Quantitative method of research was implemented using descriptive statistics to analyze data. Questionnaire was used to answer the specific problems; interview was conducted to validate the results of the study. Random sampling technique identified the respondents of the study from selected colleges and universities in the Cordillera Region. The extent of intervention programs, policies, and activities for teachers are moderately observed.